Distribution of Viral Antigen and Inflammatory Lesions in the Central Nervous System of Cockatiels (Nymphicus hollandicus) Experimentally Infected with Parrot Bornavirus 2. Issue 1 (January 2019) - de Araujo, Jeann Leal; Rodrigues-Hoffmann, Aline; Giaretta, Paula R.; Guo, Jianhua; Heatley, Jill; Tizard, Ian; Rech, Raquel R.
Neurotropism is a striking characteristic of bornaviruses, including parrot bornavirus 2 (PaBV-2). Our study evaluated the distribution of inflammatory foci and viral nucleoprotein (N) antigen in the brain and spinal cord of 27 cockatiels ( Nymphicus hollandicus ) following experimental infection with PaBV-2 by injection into the pectoral muscle. Tissue samples were taken at 12 timepoints between 5 and 114 days post-inoculation (dpi). Each experimental group had approximately 3 cockatiels per group and usually 1 negative control. Immunolabeling was first observed within the ventral horns of the thoracic spinal cord at 20 dpi and in the brain (thalamic nuclei and hindbrain) at 25 dpi. Both inflammation and viral antigen were restricted to the central core of the brain until 40 dpi. The virus then spread quickly at 60 dpi to both gray and white matter of all analyzed sections of the central nervous system (CNS). Encephalitis was most severe in the thalamus and hindbrain, while myelitis was most prominent in the gray matter and equally distributed in the cervical, thoracic, and lumbosacral spinal cord. Our results demonstrate a caudal to rostral spread of virus in the CNS following experimental inoculation of PABV-2 into the pectoral muscle, with the presence of viral antigen and inflammatory lesions first in the spinal cord and progressing to the brain.